The decision-making of high-level volleyball setters in the 2021-2022 volleyball men`s Superliga: Does the opponent matter? - Nascimento, M. H.; Laporta, L.; Ferreira Pedrosa, G.; Rocha, A. C. R.; Barbosa de Lira, C. A.; Hebling Campos, M.; da Silva Guimarães, J.; Leonardi, T. J.; Rodrigues, M. C. J.; Savassi Figueiredo, L.; de Oliveira Castro, H.; De Conti Teixeira Costa, G. (Perceptual and Motor Skills, 2023)
Our primary objective in this study was to investigate the offensive strategies employed in the attack phase of men`s volleyball, specifically focusing on side-out as stratified by the type of confrontation that was determined by the opponent`s team performance. We analyzed 5524 attacking actions during 22 games of the 12 teams that participated in the Volleyball Men`s Superliga (season 2021-2022). Based on their final rankings in the championship, we classified these teams into three tiers: high-performance, intermediate-performance, and low-performance. Subsequently, we examined the dynamics of these matches using Social Network Analysis. We found that the opponent teams' performance levels did not influence the game dynamics. Notably, the eigenvector values were prominently higher for Attack Zones 2 and 4, wherein the middle-blocker jumped to attack close to the setter across all networks. Thus, setters opted for traditional and low-risk strategies to minimize errors, disregarding available information about the skill level of the opposing team, making their offensive tactics predictable.